Kohesi Konjungtor dalam Wacana Narasi Bahasa Toraja - . Jerniati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
This writing discusses about grammatical cohesion used by the speaker in constructing the unity of discourse, focused on the markness of cohesion of conjunctor found in narrational discourse of Toraja. This writing is analyzed using theory of cohesion and intended to describe cohesion of conjunctor found in narrational discourse of Toraja. Found conjunctors are 1) addition of conjunctor, 2) period of conjunctor, 3) conclusion of conjunctor, 4) condition of conjunctor, 5) validity of conjunctor, and 6) causality of conjunctor.